A comparative study of key quality performance indicators in anesthesia and surgery in operation theatre at a tertiary care hospital in Rishikesh - Bhavna Gupta; Sanjay Agrawal; Anubha Agarwal (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: A Key Performance Indicator (KPI) is a critical metric measuring organizational success or specific activities, reflecting the periodic achievement of operational goals aligned with strategic objectives. Material and Methods: A retrospective cross-sectional study of key quality performance indicators, (CQI-NABH) concerning anesthesia and surgical services was conducted at a tertiary care hospital after taking institutional ethical clearance (AIIMS/IEC/21/150). It was as per COP 13, COP 14, and COP 15 standards of NABH 4th edition published in 2015. The study was conducted at the department of anesthesiology at a tertiary care hospital, and data were retrospectively analyzed from 01 October 2019, till November 2020. All patients undergoing elective or emergency surgical procedures under monitored anesthesia care and regional or general anesthesia during the study period were considered.The primary objective was to analyze Continuous Quality Improvement (CQI) in perioperative services, with secondary goals including gap identification, suggesting corrective actions, and examining quality indicators during the COVID-19 pandemic in 2020. Results: Out of 8574 patients operated during the study, 6705 were in the four months before the pandemic, and 1869 were operated during the COVID-19 scenario. In the pre-COVID era, many of the cases were performed on an elective basis (71.23%), and emergencies constituted 16.9% of the total number of cases. In the COVID era, most of the cases were emergencies (45.4%) and semi-emergencies (40.25%), and elective cases were only 14.05% of the total cases performed. The percentage of modification of anaesthesia plans ranged from 0-3.34%. Adverse anaesthesia events were observed in 0-2.1%, primarily related to cardiovascular, respiratory, and airway issues. No anaesthesia-related mortality was reported. Prophylactic antibiotic administration within one hour of surgery ranged from 88-100%. Conclusions: Monitoring and evaluating healthcare performance, specifically through KPIs, is vital for optimizing care and resource utilization. These indicators provide an overview of hospital service efficiency, aiding in key areas such as patient treatment, satisfaction, healthcare quality improvement, cost reduction, and optimal resource utilization. Addressing identified issues ensures effective and sustainable quality improvement in anaesthesia services, emphasizing ongoing monitoring as a foundation for hospital quality assurance.